Severe Fever with Thrombocytopenia Syndrome, Japan, 2013–2017 - Kobayashi, Yusuke; Kato, Hirofumi; Yamagishi, Takuya; Shimada, Tomoe; Matsui, Tamano; Yoshikawa, Tomoki; Kurosu, Takeshi; Shimojima, Masayuki; Morikawa, Shigeru; Hasegawa, Hideki; Saijo, Masayuki; Oishi, Kazunori (Emerging infectious diseases, 2020)
We conducted an epidemiologic study of severe fever with thrombocytopenia syndrome (SFTS) in Japan during 2013-2017. Of 303 cases reported during that period, 133 (44%) were included in this study. The median time between onset of illness and diagnosis of SFTS shortened, from 11.5 to 3.0 days, but the case-fatality rate remained high, at 27%. In 64 patients (48%), a close contact with companion animals was reported within 2 weeks of disease onset. Of these 64 patients, 40 were surveyed further, and we confirmed that 3 had direct contact with body fluids of ill companion animals; 2 had direct contact with the saliva of an ill feral cat or pet dog. These patients reported no history of tick bite, suggesting that ill companion animals might be a source of SFTS virus transmission. Direct contact with the body fluids of ill companion animals should be avoided.